Developing and testing transferability and feasibility of a model for educators using simulation-based learning — A European collaboration. (November 2017) - Bøje, Rikke Buus; Bland, Andrew; Sutton, Andrew; Hartvigsen, Tina; Hannula, Leena; Koivisto, Jaana Maija; Raussi-Lehto, Eija; Prescott, Stephen
Abstract: Background: There is a pragmatic and often inconsistent approach of embedding simulation-based learning into nursing programmes. This paper details a European collaboration that designed a model for educator facilitation for educators utilizing simulation-based education. Objectives: The objectives of the study were to develop a model to educate the educators who deliver simulation-based learning and to test to which extent this model could be transferred to education providers in different national settings. Methods: This model, its transferability and feasibility, was tested across three European countries. Educators from three Schools of Nursing participated in the study. Design-based Research was used as an overall methodology. Data were collected by the use of pre- and post-programme questionnaires and focus groups. Results: The content of the NESTLED model is consistent with the needs of the participants. The testing also demonstrated that the model is transferable across-countries. Additionally, the participants' preferences regarding amount of time and pre-reading for the different sessions vary depending on the background and level of seniority of the individual participant. Conclusion: The testing of the NESTLED model demonstrated that participants gained confidence and knowledge from undertaking the programme. Delivering the NESTLED model across-countries was found to be feasible, but flexibility is required in terms of logistical delivery of the programme. Highlights: The NESTLED model is transferable across different European educational organizations. Participants experience an increase in confidence regarding the use of simulation-based learning. A deeper understanding of learning theories enhances the ability to stand up for simulation based learning. The NESTLED model lacks emphasis on technical skills and the function of group dynamics. The model requires flexibility in terms of logistical delivery of the programme.